The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00276-017-1870-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic basis of Le Fort 1 impaction osteotomy: a radiological study

Abstract: According to our results, in impaction Le Fort 1 osteotomy, the bone resection must pass 20 mm above the alveolar border in canine area, and 15 mm above the alveolar border in molar area. The resection has to end less than 20 mm above the inferior border of the pterygomaxillary suture. The vertical height of the infraorbital foramen is a consistent landmark for repositioning of the palate in a horizontal plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Other authors observed that patients submitted to BSSO had a greater recidivation of the Sella-Nasio-Ponto B angle with greater anterior movement of Pogonium and ment than those submitted to IVRO [3].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Other authors observed that patients submitted to BSSO had a greater recidivation of the Sella-Nasio-Ponto B angle with greater anterior movement of Pogonium and ment than those submitted to IVRO [3].…”
Section: Discussionmentioning
confidence: 93%
“…Deformities can be defined as changes in the development of facial bones, especially of the maxilla and mandible, and may cause changes in other structures, organs, and systems, such as the airways [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations